Technostress, career commitment, satisfaction with life, and work-family interaction among workers in information and communication technologies = Tecno-estrés, compromiso con la carrera, satisfacción con la vida y la interacción trabajo-familia en trabajadores de la información y tecnologías de la comunicación. - Carlotto, Mary Sandra
Technostress occurs when individuals experience negative psychosocial effects of technology usage and also demonstrate negative valence associated with ICT use. It is composed of four dimensions (Disbelief, Fatigue, Anxiety, and Ineffectiveness), which describe two aspects of technostress (Technoanxiety and Technofatigue). This study aimed to investigate the relation between technostress dimensions, career commitment, life satisfaction, and work-family interactions among ICT professionals. Variables including gender, age and length of employment were also considered. The sample was composed of 234 Brazilian individuals. It was found that work-family and family-work conflicts were associated with increased technofatigue and technoanxiety, and decreased career resilience. Age and gender differences were also identified. These differences emphasize the role of organizations and society in what refers to reduce inequalities in workplace and to support better preventive actions.